MEDIA CELLULER (HP): FUNGSINYA DALAM PENYAMPAIAN PESAN-PESAN DAKWAH - Hamiruddin , (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
Since the Prophet Muhammad was sent to deliver the message, media has become an important element of it. At the level of the da'wah implementation process, the media is one of the elements that always accompanies. Therefore, the media becomes one of the primary needs in delivering da'wah messages, especially in an effort to reach all layers and regions of mad'u. In the era of advances in information communication technology, communication media are increasingly sophisticated such as cellular media (HP), so that with the vast area of da'wah, it can be reached with the help of cellular media in the form of SMS via cellular cellphone.